From waste product to blood, brains and narratives: developing a pluralist sociology of contributions to health research. Issue 3 (1st March 2018) - Boylan, Anne‐Marie R.; Locock, Louise; Machin, Laura
Abstract: The aim of this paper is to examine the meaning of the concept of donation in health research. Drawing on a set of narrative interviews with people invited to donate biosamples for research and a range of other studies, we identify several conceptual themes that speak to the complexity of the current landscape of critical thinking about donation. These conceptual themes are: the language of 'donation'; a hierarchy of biosamples; alternative informational value; narratives as donation; coincidental donation, convenience and degree of invasiveness; and rights, consent and benefits of research participation. We call for a reconceptualisation of research donation to encompass not only the numerous types of sample readily classed as donations, but also other types of data and contributions, including narrative interviews, psychometric data, patient‐reported outcome measures, record‐linkage, and time and effort. We argue for the development of a pluralist sociology of research donations, and suggest that a 'sociology of research contributions' might better capture this complexity.